Melanotic neuroectodermal tumor of infancy: A rare case report - Joyce Sequeira; Vinayakrishna Kolari; Sham Bhatt; Pallavi Sabarad; Shruti Gona Rao (Wolters Kluwer Medknow Publications, 2018)
Melanotic neuroectodermal tumor of infancy (MNTI) is a very rare neoplasm of infants seen in the oral cavity at or around birth. It shows rapid expansile growth which necessitates proper diagnosis and management. A 6.5-month-old female child reported with a swelling in the maxillary anterior alveolus, which was rapidly increasing in size and was asymptomatic. Radiographic examination showed a diffuse osteolytic radiolucent lesion in the anterior maxillary region and displacement of the developing primary tooth buds. Ultrasonography report revealed well-defined cystic lesion with calcifying foci within and with no internal vascularity. Wide surgical excision under general anesthesia was performed. Histopathological report revealed a nonencapsulated mass composed of a dual population of small round blue cells and larger melanin-containing epithelial cells in a dense cellular fibrous stroma. Tumor is seen to entrap mature bony trabeculae and soft tissue on the whole favoring a diagnosis of MNTI. Early recognition and regular follow-up is the key to successful treatment.